The media's agenda setting in manipulating audience's psychology through Ferdy Sambo's case - Ira Lusiawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The media not only presents the text written in the script that is distributed throughout its network, but also highlights dramatic elements that serve as